Case Report: T-Dxd plus bevacizumab in a patient with brain metastases from rectal cancer with HER2 amplification - Jia, Yanan; Li, Xueqin; Chen, Huisheng; Wu, Lisha; Zeng, Yinduo; Qin, Tao (Frontiers in Oncology, 2025)
Brain metastasis from colorectal cancer was more common in patients with HER2 amplification. Here, we document a 53-year-old male with HER2-amplified rectal cancer and brain metastases, treated with Trastuzumab Deruxtecan (T-Dxd, 5.4 mg/kg) plus bevacizumab (7.5 mg/kg) every three weeks as third line therapy. The patient achieved a partial response with a progression-free-survival of 7 months, highlighting the potential of T-Dxd. Adverse events included grade 3 thrombocytopenia, grade 2 neutropenia, and grade 1 fatigue. Our report emphasizes the rarity of brain metastases in colorectal cancer and illustrates a favorable response to T-Dxd plus bevacizumab.